2003
DOI: 10.1007/s10194-003-0047-4
|View full text |Cite
|
Sign up to set email alerts
|

Cluster headache in childhood and adolescence: one-year prevalence in an out-patient population

Abstract: A multicenter one-year study was carried out on 6629 headache patients under 18 years of age, attending 27 centers and clinics devoted to headache in Italy to identify the prevalence of cluster headache (CH) in childhood and adolescence. Two male CH patients aged 9 and 17 years were identified. Their attacks fulfilled the IHS criteria for CH, and they were classified as having cluster headache with undetermined periodicity and episodic cluster headache, respectively. The one-year prevalence in this headache ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
13

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 21 publications
(18 reference statements)
2
30
1
13
Order By: Relevance
“…3-18 years), since several cases with onset under 10 years have been reported (5,6,8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Genetic factors appear to be involved in the same proportion as in the adult population, as a pedigree positive for CH has been found in approximately 10% of cases, whereas a pedigree positive for migraine-type headache was found in 25% of cases. Male : female ratio seems to show almost the same proportion (M : F~3.2:1) as in adulthood.…”
Section: Discussionmentioning
confidence: 91%
“…3-18 years), since several cases with onset under 10 years have been reported (5,6,8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Genetic factors appear to be involved in the same proportion as in the adult population, as a pedigree positive for CH has been found in approximately 10% of cases, whereas a pedigree positive for migraine-type headache was found in 25% of cases. Male : female ratio seems to show almost the same proportion (M : F~3.2:1) as in adulthood.…”
Section: Discussionmentioning
confidence: 91%
“…According to these data, the most effective symptomatic treatments are oxygen and sumatriptan [6]. Prophylactic treatments tried in literature are methysergide, prednisone/prednisolone, verapamil, and flunarizine [7]. No controlled study has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 18-year-old Swedish Army recruits, prevalence was only 0.09% [14]. In a multicenter pediatric study, only two cases of CH were seen among 6629 children and adolescents attended in 27 Italian headache centers [15]. Nonetheless, if a first-degree relative is affected, chances of CH increase by up to 14-fold.…”
Section: Cluster Headachementioning
confidence: 97%
“…A recent systematic review found that only 80 cases of CH in children have been reported [15][16][17][18][19][20]21••], and many of them did not meet the full ICHD-II diagnostic criteria for CH. In many, pain was described as bilateral, while others responded to propranolol or other migraine preventive medications, raising the question whether CH has a different phenotype in children or if diagnostic issues exist.…”
Section: Cluster Headachementioning
confidence: 99%